The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijerph19063518
|View full text |Cite
|
Sign up to set email alerts
|

“When She Says Daddy”: Black Fathers’ Recidivism following Reentry from Jail

Abstract: We report on the findings of a mixed methods longitudinal study of 84 African American fathers of young children who were enrolled into the study during the father’s jail stay. Participants were assessed using interviews, self-report measures, and administrative records on frequency of father–child contact, father–caregiver relationship quality, family support, paternal pre-incarceration employment, fathers’ plans to live with the child upon reentry, history of substance abuse, and new convictions one year fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Factors, such as social support can attenuate risks faced by Black fathers, including some of the most marginalized subsets of fathers—Black nonresident fathers, and formerly incarcerated Black fathers. In fact, some research suggests that better health outcomes like reduced depressive symptoms (Tsuchiya et al, 2018), more positive reentry experiences, and lower reincarceration rates (Thomas et al, 2022) are all linked to fathers receiving high levels of positive social support.…”
Section: Thematic Contributionsmentioning
confidence: 99%
“…Factors, such as social support can attenuate risks faced by Black fathers, including some of the most marginalized subsets of fathers—Black nonresident fathers, and formerly incarcerated Black fathers. In fact, some research suggests that better health outcomes like reduced depressive symptoms (Tsuchiya et al, 2018), more positive reentry experiences, and lower reincarceration rates (Thomas et al, 2022) are all linked to fathers receiving high levels of positive social support.…”
Section: Thematic Contributionsmentioning
confidence: 99%
“…Recent work indicates that the frequency, modality, and quality of parent–child contact during parental incarceration are all important factors for both parents and children (Cramer et al, 2017). Studies focusing on incarcerated parents have found that more parent–child contact during incarceration, usually in the form of phone calls and visits, is associated with more engaged parent–child relationships during reentry, as well as better parental mental health and lower recidivism (e.g., McKay et al, 2019; Thomas et al, 2020; Visher et al, 2013). This is even true to some degree for video visits (Duwe & McNeeley, 2020).…”
Section: The Importance Of Visits and Other Forms Of Contact For Inca...mentioning
confidence: 99%
“…This further led to the destruction of families, as women and children in low-income communities were left to cope without husbands and fathers (Western & Wildeman, 2009). The systemic oppression of African American men has led to more than 1.1 million imprisoned in the United States, with approximately 500,000 being fathers between 25-29 years of age (Modecki & Wilson, 2009;Thomas et al, 2022). In 2017, African American men were sentenced six times more than white men (Thomas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The systemic oppression of African American men has led to more than 1.1 million imprisoned in the United States, with approximately 500,000 being fathers between 25-29 years of age (Modecki & Wilson, 2009;Thomas et al, 2022). In 2017, African American men were sentenced six times more than white men (Thomas et al, 2022). In 2021, The Sentencing Project estimated that 1 in 12 African American men are in prison or jail on any given day, and 1 in 3 are at risk of going to prison in their lifetimes (The Sentencing Project, 2021).…”
Section: Introductionmentioning
confidence: 99%